2015
DOI: 10.1186/s12906-015-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kolaviron on hepatic oxidative stress in streptozotocin induced diabetes

Abstract: BackgroundAlteration in antioxidant defence and increase in oxidative stress that results in tissue injury is characteristic of diabetes. We evaluated the protective effects of kolaviron (a flavonoid complex extracted from the seeds of Garcinia kola) on hepatic antioxidants, lipid peroxidation and apoptosis in diabetic rats.MethodsTo induce diabetes, rats were injected with streptozotocin intraperitoneally at a single dose of 50 mg/kg. Kolaviron (100 mg/kg) was administered orally for 6 weeks (5 times weekly).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Therefore, consumption of its stores by CCl 4 -induced scavenging free radicals is indicative of liver injury [57]. Glutathione peroxidase (GPX) plays a pivotal role in protective defense system in the liver [58]. Diminished activity of GPX, due to ROS, is also another manifestation of propagated liver injury.…”
Section: -Induced Hepatotoxicitymentioning
confidence: 99%
“…Therefore, consumption of its stores by CCl 4 -induced scavenging free radicals is indicative of liver injury [57]. Glutathione peroxidase (GPX) plays a pivotal role in protective defense system in the liver [58]. Diminished activity of GPX, due to ROS, is also another manifestation of propagated liver injury.…”
Section: -Induced Hepatotoxicitymentioning
confidence: 99%
“…In addition, the ORAC index (oxygen radical absorbance capacity), the reduced glutathione (GSH) level, the reduced oxidized glutathione ratio (GSH: GSSG) and catalase (CAT) activity were decreased in the diabetic rat liver. The TUNEL assay showed an increase in apoptotic cell death in the livers of these animals 21 . In using TBARS as a measure of lipid peroxidation in lung tissue, a significant increase was seen in the diabetic animals in comparison with the experimental group and control group (healthy animals).…”
Section: ■ Discussionmentioning
confidence: 85%
“…To this end, Iqbal et al assessed the anthelmintic activity of N. tabacum leaves using live Haemonchus contortus (in vitro study) and in vivo testing by applying sheep naturally infected with mixed infection of gastrointestinal nematodes [37]. Fresh leaf of N. tabacum was obtained from the local market, identified by a botanist and crude extract of the leaves prepared according to previously described method using methanol and water [38]. In vitro study, the effectiveness of water and methanol extract of the plant is observed in the mortality of the worms when compared to a levamisole -a standard anthelmintic drug.…”
Section: Anthelmintic Activity Of N Tabacummentioning
confidence: 99%